Dose optimization of vancomycin in obese patients: A systematic review - Elrggal, Mahmoud E.; Haseeb, Abdul; AlGethamy, Manal; Ahsan, Umar; Saleem, Zikria; Althaqafi, Areej Sultan; Alshuail, Sattam Saad; Alsiddiqi, Zohair Ahmad; Iqbal, Muhammad Shahid; Alzahrani, Albaraa Faraj; AlQarni, Abdullmoin; Radwan, Rozan Mohammad; et al. (Frontiers in Pharmacology, 2023)
Background: Dose optimization of vancomycin plays a substantial role in drug pharmacokinetics (PK) because of the increased incidence of obesity worldwide. This systematic review was aimed to highlight the current dosing strategy of vancomycin among obese patients. Methods: This systematic review was in concordance with Preferred Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines. The literature search was carried out on various databases such as Scopus, PubMed/MEDLINE, ScienceDirect and EMBASE using Keywords and MeSH terms related to vancomycin dosing among obese patients. Google Scholar was also searched for additional articles. The English language articles published after January, 2000 were included in this study. The quality of the study was assessed using different assessment tools for cohort, case reports and randomized clinical trials. Results: A total of 1029 records were identified. After screening, 18 studies were included for the final review. Of total, twelve studies are retrospective and remaining six are case-control studies. A total of eight studies were conducted in pediatrics while remaining studies were conducted in adult population. Most of the studies reported the dosing interval every 6 to 8 hours. Differences in target trough concentration exist with respect to target ranges. Conclusion: There is an urgent need for better-defined dosing strategy in obese and overweight patients. Therefore, multi-center studies are needed to evaluate the alternate dosing strategy in overweight or obese patients and assess how obesity and overweight affects the PK parameter to increase the efficacy, reduced side effects and promote antibiotic cost savings.